Important Trends of Biomedical Engineering for Ukrainian Health Care - Maksymenko, V. B.; BiloshytskaО. К.; Ovcharenko, G. R.; Yurjeva, K. A. (Transplantation and artificial organs, 2021)
The analysis of the urgent tasks of biomedical engineering is carried out and questions are formulated that need to be addressed at the state level, which will significantly increase the efficiency, safety and quality of healthcare, increase the profitability of operating expensive equipment, and will contribute to the revival of domestic production of medical equipment and materials and the implementation of EU regulations.